The osteoprotective effect of Herba epimedii (HEP) extract in vivo and in vitro. Issue 3 (2005) - Xie, Fang; Wu, Chun-Fu; Lai, Wan-Ping; Yang, Xu-juan; Cheung, Pik-Yuan; Yao, Xin-Sheng; Leung, Ping-Chung; Wong, Man-Sau
Abstract : Herba epimedii (HEP) is one of the most frequently used herbs prescribed for treatment of osteoporosis in China. In the present study, the in vivo effects of HEP extract on bone metabolism were evaluated using 4-month-old ovariectomized (OVX) or sham-operated (Sham) female Sprague-Dawley rats orally administered with HEP extract (110 mg kg−1d−1), 17ß-estrogen (2 mg kg−1d−1) or its vehicle for 3 months. HEP extract significantly decreased urinary calcium excretion, suppressed serum alkaline phosphatase (ALP) activity and urinary deoxypyridinoline levels in OVX rats ( P < 0.05 versus vehicle-treated OVX rats). Histomorphometric analysis indicated that HEP extract could prevent OVX-induced bone loss by increasing tibial trabecular bone area and decreasing trabecular separation in OVX rats ( P < 0.05 versus vehicle-treated OVX group). The in vitro effects of HEP extract were also studied using rat osteoblast-like UMR 106 cells. HEP extract significantly stimulated cell proliferation in a dose-dependent manner ( P < 0.01 versus vehicle-treated) and increased ALP activity at 200 μgml−1 ( P < 0.01 versus vehicle-treated) in UMR 106 cells. It modulated osteoclastogenesis by increasing osteoprotegrin (OPG) mRNA and decreasing receptor activator of NF-κB ligand (RANKL) mRNA expression, resulting in a dose-dependent increase in OPG/RANKL mRNA ratio ( P < 0.01 versus vehicle-treated). Taken together, HEP treatment can effectively suppress the OVX-induced increase in bone turnover possibly by both an increase in osteoblastic activities and a decrease in osteoclastogenesis. The present study provides the evidence that HEP can be considered as a complementary and alternative medicine for treatment of post-menopausal osteoporosis.